A build-or-lease case study for a potential new warehouse due to increasing storage capacity requirements - Denis Daus (2018)
© IEOM Society International. A build-or-lease decision for warehouse is a crucial success factor for future product availability. The research deals with a logistics study for a crop science company. The need for it stems from increasing production volumes which cause storage space shortages and high warehouse utilizations. Before deciding for or against a warehouse, it has to be analyzed how much storage space is required and where the new warehouse should be located. The research evaluates if it is preferable to either build or lease a potential new warehouse. A comprehensive literature review reveals considerations for carrying out logistics studies by means of a potential analysis. A database serving as a material requirements planning tool calculates future storage requirements based on a worst case scenario. The optimal warehouse location was found by means of the heuristic center-of-gravity technique. A sensitivity analysis has been applied for the economic evaluation. The research concludes with a recommendation on the most economical alternative, which is to lease a warehouse with 1085 pallet places at the determined optimal location. The research considers static data only. Further research should consider dynamic behavior of the system, or factors which are typical for the industry (e.g. environmental impact, morality). © IEOM Society International.